Immunogenic cell death related risk model to delineate ferroptosis pathway and predict immunotherapy response of patients with GBM - Feng, Songshan; Liang, Xisong; Li, Jing; Wang, Zeyu; Zhang, Hao; Dai, Ziyu; Luo, Peng; Liu, Zaoqu; Zhang, Jian; Xiao, Xiaoxiong; Cheng, Quan (Frontiers in Immunology, 2022)
Immunogenic cell death (ICD) is a form of cell death that leads to the regulation and activation of immune response, which is characterized by the exposure and release of damage‐associated molecular patterns (DAMPs) in the tumor microenvironment. Accumulating evidence has revealed the significance of ICD related genes in tumor progression and therapeutic response. In this study, we obtained two ICD related clusters for glioblastoma (GBM) by applying consensus clustering, and further constructed a risk signature on account of the prognostic ICD genes. Based on the risk signature, we founded that higher risk scores were associated with worse patient prognosis. Besides, the results illustrated that ferroptosis regulators/markers was highly enriched in high-risk group, and ferroptosis were correlated with cytokine signaling pathway and other immune related pathways. We also discovered that high risk scores were correlated to specific immune infiltration patterns and good response to immune checkpoint blockade (ICB) treatment. In conclusion, our study highlights the significance of ICD related genes as prognostic biomarkers and immune response indicators in GBM. And the risk signature integrating prognostic genes possessed significant potential value to predict the prognosis of patients and the efficacy of ICB treatment.